ANALISIS KESESUAIAN MATERI AJAR DENGAN TES HASIL BELAJAR MAHASISWA DI LINGKUNGAN FKIP UHN MEDAN. - Suryati Sitepu (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2020)
This research is a type of evaluation research conducted using qualitative methods. This research will be conducted at the Teaching and Education Faculty of the University of HKBP Nommensen. The time for conducting this research is the odd semester of the 2019/2020 school year. Plans that will participate in this research are Lecturers of FKIP UHN Medan. The sample chosen in this study was one lecturer who worked on each odd semester course at FKIP UHN by taking a sample with a random sampling technique. This study aimed to explain the topic and the suitability of the material submitted with material given to students by lecturers of Mathematics Education Study Program UHN Medan FKIP 2019/2020 Academic Year. The results showed that: 1) Overall syllabus conformity with teaching materials approved by lecturers from each study program at FKIP UHN was 99,428. It can be concluded that the learning objectives based on PBM carried out by lecturers in FKIP UNH are already